Case report: Refractory focal motor seizure associated with cerebrospinal fluid neurochondrin antibody - Ahmad, Rowaid; Huang, Yumeng; Wang, Peter R.; Masel, Todd; Li, Xiangping (Frontiers in Immunology, 2024)
The Neurochondrin-associated neurological disorder is rare and its principal clinical manifestations observed so far are cerebellar ataxia, rhombencephalitis, and hyperkinetic movements such as chorea. Neurochondrin antibody-associated Autoimmune Epilepsy (AE) has not been previously reported in the literature. This is the first reported case of refractory autoimmune epilepsy with positive CSF anti-neurochondrin antibody. This study reveals an under-recognized role of neurochondrin antibody in epilepsy.